A new hand-eye calibration approach for fracture reduction robot. (31st October 2017) - Wang, Lifeng; Wang, Tianmiao; Tang, Peifu; Hu, Lei; Liu, Wenyong; Han, Zhonghao; Hao, Ming; Liu, Hongpeng; Wang, Kun; Zhao, Yanpeng; Guo, Na; Cao, Yanxiang; et al.
Abstract: Objective: The hand-eye calibration is used to determine the transformation between the end-effector and the camera marker of the robot. But the robot movement in traditional method would be time-consuming, inaccurate and even unavailable in some conditions. The method presented in this article can complete the calibration without any movement and is more suitable in clinical applications. Methods: Instead of solving the classic non-linear equation AX = XB, we collected the points on X and Y axes of the tool coordinate system (TCS) with the visual probe and fitted them using the singular value decomposition algorithm (SVD). Then, the transformation was obtained with the data of the tool center point (TCP). A comparison test was conducted to verify the performance of the method. Results: The average translation error and orientation error of the new method are 0.12 ± 0.122 mm and 0.18 ± 0.112° respectively, while they are 0.357 ± 0.347 mm and 0.416 ± 0.234° correspondingly in the traditional method. Conclusions: The high accuracy of the method indicates that it is a good candidate for medical robots, which usually need to work in a sterile environment.